Carbohydrate metabolism during active and passive post-exercise recovery - Peters, Edith M (MRC/UCT RU for Exercise and Sport Medicine, 2017)
It is known that light muscular activity performed during the immediate post-exercise recovery period, increases the rate at which lactate and protons are removed from the circulation. This study examined the effect which this light activity had on muscle glycogen and lactate levels, as well as the restoration of blood fuel and hormonal homeostasis. A further dimension of the study was to monitor the metabolic adaptations which took place in the inactive leg during light one-legged post-exercise activity. Eight subjects participated in this study. The testing procedure involved three phases: the assessment of each subject's maximal exercise capacity on the cycle ergometer; the imposition of an intense intermittent exercise protocol which was followed by a passive recovery of 90 minutes; and lastly, the repetition of the exhaustive intermittent protocol followed by a partially-active recovery phase during which the subject cycled with one leg at approximately 30 percent of two-legged VO2. max. for the first 45 minutes of the 90-minute recovery period. During the latter two phases, blood samples and muscle biopsies were taken at rest and during the post-exercise recovery. The light one-legged activity expedited the return of blood lactate and pH levels to basal values (p < 0,01), during the initial 30 minutes of recovery but slowed down the removal of lactate and protons during the latter 15 minutes of the active recovery. There were no significant differences in the blood glucose, pyruvate, alanine, and insulin levels during the different recovery protocols, but plasma glucagon levels were significantly lower <p<0,01) during the active recovery. The major finding was that glycogen resynthesis was not significantly 0,05) delayed as a result of activity during the immediate post-exercise period, but that muscle lactate levels were significantly lower in the passive leg than in the active leg after the first 45 minutes of the recovery period. As resynthesis of glycogen took place during the active recovery, this study appeared to indicate (i) that lactate oxidation was an important source of substrate during the initial 30 minutes of the active recovery (ii) that oxidation was possibly the primary fate of lactate during the active post-exercise recovery period and (iii) that intramuscular glyconeogenesis in the fast-twitch muscle fibres of the previously active legs was a distinct possibility. Apparent suprabasal production of lactate in the active fibres of the active leg during the latter stages of the active recovery, however, appeared to indicate partial reliance on exogenous glucose as substrate in these fibres during this stage of the recovery.